2018
DOI: 10.1007/s11011-018-0306-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antidepressant-like effects of Eugenia catharinensis D. Legrand in an animal model of depression induced by corticosterone

Abstract: This work investigated the antioxidant and antidepressant-like effects of ethyl acetate extract from Eugenia catharinensis in mice treated with corticosterone (20 mg/Kg). The animals received saline or corticosterone (21 days) and, in the last 7 days, they were treated with the extract (50, 125, 200 or 250 mg/Kg) or vehicle. After 24 h, the mice were submitted to the open field and forced swimming tests, after which the hippocampus and cerebral cortex were removed. Our results showed that the extract decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…An increasing body of evidence points to the role of oxidative stress in changing the neuronal plasticity that accompanies MDD, and thus the potential role of antioxidants in the management www.nature.com/scientificreports www.nature.com/scientificreports/ of depression 31 . Recent evidences confirmed that some antidepressants, like fluoxetine and mirtazapine, possess antioxidant activities 5,20,[31][32][33] . In accordance, many strong well-known antioxidants showed to have antidepressant activity, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence points to the role of oxidative stress in changing the neuronal plasticity that accompanies MDD, and thus the potential role of antioxidants in the management www.nature.com/scientificreports www.nature.com/scientificreports/ of depression 31 . Recent evidences confirmed that some antidepressants, like fluoxetine and mirtazapine, possess antioxidant activities 5,20,[31][32][33] . In accordance, many strong well-known antioxidants showed to have antidepressant activity, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic acids are naturally found in fruits and vegetables, and are endowed with a wide spectrum of bioactivities such as: antidepressant [49], antihypertensive [50], antiinflammatory [51], neuroprotective [51], antihyperglycemic [52], anticancer and antidiarrheal [53].…”
Section: Distribution In Plants and Biological Activitiesmentioning
confidence: 99%
“…Analysis of the extract using HPLC-ESI-MS/MS demonstrated the presence of several phenolic compounds, mainly phenolic acids, such as p-coumaric acid, ferulic acid, and caffeic acid. The authors suggest that chemical constituents are the active principles of antidepressant action [54]. Antidepressant action also was demonstrated for butanol fraction of Olax subscorpioidea Oliv.…”
Section: Antidepressant Activity Of Cinnamic Acidsmentioning
confidence: 87%